Instantaneous drag increase on alternate transverse superhydrophobic strips. (January 2021) - Wang, Xingwei; Bao, Luyao; Yang, Wufang; Zhang, Jianbin; Qu, Minghai; Hu, Haibao; Zhou, Feng; Liu, Weimin
Abstract: In the present work, drag increase (DI) is obtained on superhydrophobic surface. The experiments were carried out with a Taylor-Couette rotor with their surface being coated by alternate superhydrophobic and hydrophilic strips in spanwise. The results exhibit a transition Re ( Re T ) dividing DI into two stages. Before Re T, the DI is very inconspicuous, but after Re T, DI rises sharply and then remains significant. The mechanism is proposed and also verified by numerical simulation. Before Re T, the deformation of air layer on superhydrophobic surface is slight and thus generates inconspicuous capillary force. After Re T, the receding contact line detaches from the edge of superhydrophobic surface leading to the air layer deforms more easily resulting in significant capillary force therefore DI is significant. Graphical abstract: Image 1 Highlights: The drag increase phenomenon is observed on alternate superhydrophobic and hydrophilic stripes. The drag rises sharply at a critical Reynolds number because of the depinning of receding three-phase contact line. Significant drag at high Reynolds number is caused by capillary force stemming from deformed air layer.